‘Popish Pelagianism’ or the Work of Divine Providence?: A Re-evaluation of John Wesley’s Theology of Prevenient Grace - Wood, Joseph (The Evangelical quarterly, 2022)
Responding to John Piper’s book, Providence (2020), and building on the work of Howard Snyder, this article articulates a Wesleyan-Arminian theology of ‘prevenient grace’. Highlighting Philippians 2:12–13, prevenient grace is articulated as a theological concept, rooted in the Bible, clearly expressed in the writings of James Arminius and made more widely accessible by the teaching of John Wesley. The theology of prevenient grace has been debated through the centuries and continues to be a primary point of distinction between those who would align their thinking to John Calvin (and Calvinism), in opposition to those who align with the teachings of John Wesley (and Wesleyan/Arminianism). From the perspective of God’s providence, the article identifies the slight, yet profound, difference between irresistible and prevenient grace. It argues that the caricature of Arminius’s, and therefore, Wesley’s teaching as Pelagian is unfounded. It concludes with suggestions of how the theology of prevenient grace offers a helpful framework for pastoral care.